TINGKAH LAKU LOBSTER PASIR (Panulirus homarus) YANG DIPELIHARA PADA SHELTER BERBEDA - dudi lesmana; Fia Sri Mumpuni (JURNAL MINA SAINS, 2021)
Efforts are being made to reduce the high rate of cannibalism by using shelters in their maintenance of cages. Shelters are needed as a hiding place for moulting of lobsters, as well as expanding the living area. The aims of this study was to determine the behavior of spiny lobster including the frequency of molting and the level of cannibalism. This research took place in July–October 2021, at the Vocational School, IPB University. The design used in this research was a completely randomized design (CRD) using 4 treatments and 3 replications. The treatments in this study consisted of rearing of lobster with box-hole brick shelter (A), rearing of lobster with round hole brick shelter (B), rearing of lobster with pipe shelter (C) and rearing of lobster without shelter (K). The molting frequency of lobsters reared with box-hole shelters tended to be higher (60.0%) than other treatments but not significantly different (P>0.05). The percentage of cannibalism in lobsters reared without shelters / control (47.67%) tended to be higher than lobsters reared in batako shelters.